Anatomical variations in the posterior circle of willis and vascular pathologies in isolated unilateral thalamic infarction - Goerlitz, Johannes Erich; Wenz, Holger; Al-Zghloul, Mansour; Kerl, Hans Ulrich; Groden, Christoph; Förster, Alex (Journal of neuroimaging, 2015)
BACKGROUND AND PURPOSE To characterize relations between configurations of the posterior part of the Circle of Willis (CoW) and the occurrence of unilateral thalamic infarction. METHODS From a magnetic resonance imaging report database, we identified and analyzed 111 patients with acute isolated unilateral thalamic infarction on diffusion-weighted imaging (DWI). Vascular pathologies were noted on magnetic resonance angiography (MRA) and the diameter of the posterior communicating artery (PComA) and the P1 and P2 segments of the posterior cerebral artery determined. RESULTS Most infarctions were observed in the territory of the inferolateral arteries (70.2%), followed by the paramedian (16.3%), tuberothalamic (8.7%), and posterior choroidal arteries (4.8%). Relevant vascular pathologies included stenosis of the basilar artery (4.5%), P1 segment stenosis (4.5%)/occlusion (.9%), and P2 segment stenosis (14.4%)/occlusion (4.5%). Paramedian thalamic infarction was associated with ipsilateral P1 segment hypoplasia/absence (P < .001); tuberothalamic infarction with ipsilateral PComA hypoplasia/absence (P = .08). Furthermore, the diameter of the relevant CoW segment was smaller in patients with ipsilateral thalamic infarction. CONCLUSIONS Assessment of CoW configuration on MRA may be helpful to understand the appearance of unilateral thalamic stroke independent from stroke etiology. A smaller diameter of the relevant CoW segment might be a risk factor for ipsilateral thalamic stroke in the corresponding thalamic vascular territory.